Psychological empowerment, motivation and job performance amongst 5-star hotel employees in Kuala Lumpur / Dziatul Nadiah Dzia-Uddin - Dzia-Uddin, Dziatul Nadiah (2013)
Hospitality and tourism in Malaysia is growing as one of the major revenue contributor to the country's economy and moving in line with vision to make Malaysia as a high-income country. Overall, this achievement was due to effective tourism activities that have been planned by Malaysia ministry of tourism until this industry became steady. Hotel industry plays a vital role as complement to tourism as it provides accommodation to tourists. Nowadays, in an increasingly competitive global economy make hotel industry became very competitive especially in the big cities such as in Kuala Lumpur, Malaysia. In order to compete with other competitors, the hotel management needs to find ways and acts fast in order to make its hotel to be the best hotel in terms of satisfying the guests as well as the employees. One of the ways is by adopting empowerment because this approach can allow the employees to fulfill all guests’ needs and wants, and at the same time the employees will have the feeling of ownership. This study attempts to investigate the influence between psychological empowerment dimensions (meaning and self-determination) and motivation and the implication on employees job performance. The determinant of the study framework model of this study was adopted by several researchers which are Thomas and Velthouse (1990), Haozhan (2010) and Indradevi (2012).